Mode of inheritance of resistance to the stalk-eyed fly (Diopsis longicornis) in rice - Ganteh Weelar, Charles; Lamo, Jimmy; Otim, Michael Hilary; Awio, Bruno; Ochwo-Ssemakula, Mildred (International Journal of Agronomy and Agricultural Research, 2017)
Stalk eyed flies (D. longicornis and D. apicalis) are pests of economic importance on rice. Of the two species of stalk- eyed fly, D. longicornis is the most prevalent and destructive. To determine the mode of inheritance for resistance to the stalk-eyed fly in rice in Uganda, crosses were made among eight parental lines (NERICA4, TXD306, K85, NM7-22-11-B-P-1-1, NERICA1, NERICA6, NAMCHE2 and PAKISTAN) selected on the basis of their response to the stalk-eyed fly, high yield and early maturity. Of the eight, four genotypes [NERICA4, TXD306, and NM7-22-11-B-P-1-1 and K85], exhibited lower levels of deadheart occurrence and were crossed using the North Carolina II mating design with four susceptible genotypes [NERICA1 and NERICA6, PAKISTAN, and NAMCHE2]. Studies on combining abilities were conducted on 16 F1 hybrids along with the eight parents. Narrow sense coefficients of genetic determination (NSCGD) were low to moderate (0.09 - 0.33) and broad sense coefficients of genetic determination (BSCGD) were moderate to high (0.38 - 0.89) for traits studied. Both GCA and SCA effects were significant for percentage of deadhearts. However, Baker’s ratio was less than 0.5 (0.37) for deadhearts, indicating that both additive and non-additive gene effects were involved in resistance to the stalkeyed fly, although non-additive gene effects were more important. NERICA4 andK85 were found to be good general combiners for increasing resistance. The crosses Pakistan × TXD306 and NERICA1× NM7-22-11-B-P-1-1 were identified as promising lines for advancement.
Keywords: Quantitative inheritance; combining ability; Gene action; Rice